NASA Formal Methods 4th International Symposium, NFM 2012, Norfolk, VA, USA, April 3-5, 2012. Proceedings - Goodloe, Alwyn E.; Person, Suzette; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the refereed proceedings of the Fourth International Symposium on NASA Formal Methods, NFM 2012, held in Norfolk, VA, USA, in April 2012. The 36 revised regular papers presented together with 10 short papers, 3 invited talks were carefully reviewed and selected from 93 submissions. The topics are organized in topical sections on theorem proving, symbolic execution, model-based engineering, real-time and stochastic systems, model checking, abstraction and abstraction refinement, compositional verification techniques, static and dynamic analysis techniques, fault protection, cyber security, specification formalisms, requirements analysis and applications of formal techniques.
Keywords: Computer science; Software engineering; Operating systems (Computers).; Logic design; Computer Science; Software Engineering; Programming Languages, Compilers, Interpreters; Operating Systems; Logics and Meanings of Programs; Software Engineering/Programming and Operating Systems; Programming Techniques